Reconciling soil thermal and hydrological lower boundary conditions in land surface models. Issue 14 (30th July 2013) - Decharme, Bertrand; Martin, Eric; Faroux, Stéphanie
Abstract : [1] The lower boundary condition of soil in land surface models is a key parameter, which can affect the energy and water budget at the surface/atmosphere interface. Indeed, it affects the thermal inertia of the ground as well as the water fluxes from the subsurface to the river‐aquifer system. In land surface models, it is well known that the soil must be sufficiently deep to compute a realistic soil temperature profile, while in terms of hydrology, the soil column should be substantially thinner in order to simulate realistic river discharges and therefore surface fluxes. In addition to the confirmation of this paradox, the goal of this study is to show how it is solved in the Interaction between Soil Biosphere Atmosphere (ISBA) land surface model. To reconcile hydrological and thermal lower boundary conditions, a simple approach is developed in which the soil temperature profile is extended below the hydrological column of the soil, and the water profile is extrapolated at each thermal node as the depth increases. ISBA is applied across France over 20 years and at a relatively high resolution. Additional experiments are also performed using the same lower boundary conditions of 1, 2, 3, 5, and 12 m for hydrological and thermal equations. The simulated river discharges and temperature profiles are compared to a dense network of in situ observations. The results confirm the paradox addressed previously and demonstrate that, if left unsolved, it could lead to poor simulation of the soil water and energy budgets, potentially affecting the performance of forecast studies, hydrological applications, and/or climate modeling. Key Points: The lower boundary condition of soil in land surface model Important parameter for soil temperature and hydrology Evaluation over a dense network of soil temperatures and river discharges